Supply chain management: the measurement process - Prokop, Darren (Henry Stewart Talks, 2022)
Logistics, Finance, Return on Assets, Return on Sales Ratio, Net income, Debt financing, Operating costs, Profit margins, Acid Test Ratio, Cash to cash cycle